REVIEW LITERATURE: MENGKAJI PEMBERIAN PIJAT BAYI DENGAN MUROTTAL AL-QUR’AN UNTUK MENINGKATKAN DURASI TIDUR BAYI USIA 3-12 BULAN - Dian Wahyuningtyas (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
ABSTRACT Introduction: Most babies (44.2%) had sleep disturbances, and 72% of parents thought that this was not a significant problem. Sleep problems in babies are generally due to insufficient sleep in the baby. One of the efforts to improve baby sleep uration is by offering baby massage accompanied by the chanting of the Al-Qur'an murottal. Methods: International literature searched using electronic media by using several databases such as Google Scholar, Link Spinger and PubMed. The article used is 8 articles that discuss the effect of baby massage on baby sleep and the effect of listening to the Murottal Al-Quran on the duration of baby sleep. Results: There was a significant effect between infant massage and murottal Al-Qur'an on the increase in infant sleep duration. Discussion: One way to meet the sleep needs of babies is by increasing the duration of the baby's sleep. Efforts to increase sleep duration in babies can be done by giving baby massage accompanied by Al-Qur'an murottals. Baby massage can increase serotonin neurotansmiter levels, and listening to the murottal Al-Qur'an, the brain can produce neuropeptide substances so that it provides feedback in the form of a sense of comfort, safety, after that the baby's sleep will be more soundly. Conclusion: Baby massage with murottal Al-Qur'an is effective for increasing sleep duration in babies. Keywords: Baby massage; Murottal; length of sleep for babies